STUDENTS' PERCEPTION OF ADOLESCENTS' DRUG USE: IMPLICATION FOR SOCIAL HEALTH PROMOTION - NWAGU , EVELYN (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The purpose of this study was to examine students' perception of adolescents' drug use. Descriptive survey research design was used for the study. The instrument for data collection was a researcher made questionnaire. The population of the study comprised all secondary school students in government secondary schools in Igboetiti L.GA. of Enugu state. The data collected from the study were analysed using mean, standard deviation, t-test for independent groups and Analysis of Variance. The result showed that the students had negative perception of adolescents' drug use. There were significant differences inthe mean perception of;male andfemale students, junior and senior students and students of various age groups for most of the items on students' perception of drug use. The implications of the resultfor social health promotion were discussed and it was recommended among others that all drug education programme meant for adolescents should strive to correct the negative perception of youths that most young people abuse drugs.